RESISTENSI PRIBUMI TERHADAP DOMINASI KOLONIAL DALAM NOVEL DI TEPI KALI BEKASI: KAJIAN POSKOLONIAL EDWARD SAID - Syaifur Rohman, Moh.; Salamet; Juhdi, Moh. (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to examine the representation of native resistance against colonial domination in the novel Di Tepi Kali Bekasi by Pramoedya Ananta Toer through Edward Said's postcolonial perspective. A descriptive qualitative method with repeated reading and note-taking techniques was employed to collect data in the form of words, phrases, sentences, dialogues, and narrations representing colonial domination and native resistance. The data were analyzed through the stages of reduction, presentation, and interpretation based on Said's concept of orientalism. The findings reveal three forms of native resistance to colonial domination: physical resistance through armed struggle, native leadership as a deconstruction of orientalist stereotypes, and collective solidarity as a strategy against colonial hegemony. These three forms represent processes of identity recovery, strengthening of national consciousness, and restoration of native dignity as manifestations of deconstructing the colonial discourse constructed by the West. These findings reinforce the understanding that revolutionary literary works function as a medium of counter-narrative that reveals the complexity of power relations between colonizers and colonized societies, while affirming the relevance of Edward Said's postcolonial theory in reading Indonesian literature on the theme of the independence revolution.